FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN NEONATUS HIPERBILIRUBIN DI RSB PASUTRI BOGOR PROVINSI JAWA BARAT TAHUN 2016 - Marini Madiastuti; Sri Chalada (Jurnal Ilmu dan Budaya, 2017)
Background: Neonates Hiperbilirubin is a state resembling liver disease found in newborns due to hyperbilirubinemia and is one of urgency that often occurs in newborns, as much as 25-50% in term infants and 80% in low birth weight babies. In 2016 the period of January to June in the Pasutri Maternity Hospital Bogor Hiperbilirubin number of cases as many as 95 babies. The purpose of this study was to determine the factors related with the incidence of neonatal Hiperbilirubin in the Pasutri Maternity Hospital Bogor West Java Province. This research is a quantitative analytical research using case control design. The population in this study were all neonatus hiperbilirubin recorded in the Pasutri Maternity Hospital Bogor West Java Province. The total number of population were 1270 babys, with 95 sample cases and 95 babys for sample control. Data analysis included univariate analysis using frequency distribution and bivariate analysis using chi square to see the relationship between the variables studied. Results of univariate analysis showed age full-term pregnancies as many (55.8%), abnormal type of labor as much (57.4%), weight <2,500 g total (47.9%) and infants with male gender as (59.5%). The results of the bivariate analysis showed there are relationships between gestational age (p-value 0.009), type of delivery (p-value 0.002) and birth weight (p-value 0.000). And no relationship with gender (p-value 0.104) and the incidence Hiperbilirubin. Suggestions put forward for health officials to provide information to parents about the signs Hiperbilirubin and treatment of infants with Hiperbilirubin.